Convergence of Linear Multistep Methods and One-Leg Methods for Index-2 Differential-Algebraic Equations with a Variable Delay (Advances in Applied Mathematics and Mechanics, 2012)
Linear multistep methods and one-leg methods are applied to a class of index-2 nonlinear differential-algebraic equations with a variable delay. The corresponding convergence results are obtainedand successfully confirmed by some numerical examples. The results obtained in this work extend the corresponding ones in literature.